2017
DOI: 10.5897/jvmah2015.0424
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of frozen raw and undercooked Nile tilapia (Oreochromis niloticus) fillets and food safety practices of fish handlers in Arba Minch town, SNNPR, Ethiopia

Abstract: The study was designed to assess the microbiological quality of Nile tilapia (Oreochromis niloticus) fillets and food safety practices of fish handlers in Arba Minch town, SNNPR, Ethiopia. A questionnaire survey was conducted to assess the food safety practices of fish handlers. The microbiological quality of frozen raw and undercooked (Asa leb-leb) tilapia fillets was assessed by determining the total plate count and isolating hygiene indicator bacteria that is, Escherichia coli and other major foodborne path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
3
5
7
Order By: Relevance
“…This may be due to the negative effect of heat on the bacteria during fish origin food preparation. This was in agreement with the result of Wendwesen et al, 36 who reported 4.63×10 6 cfu/g Escherichia coli count in frozen raw Nile tilapia fish samples and a 4.92×10 3 cfu/g Escherichia coli load in asa lebleb (local name) fish origin foods in Arba Minch town, SNNPR, Ethiopia. The Escherichia coli load in raw fish sample was higher than the result of Dhanapal et al, 40 who found 4.9×10 4 cfu/g and lower than the result of Wendwesen et al, 36 who reported 4.63×10 6 cfu/g in frozen raw Nile tilapia fillet samples.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This may be due to the negative effect of heat on the bacteria during fish origin food preparation. This was in agreement with the result of Wendwesen et al, 36 who reported 4.63×10 6 cfu/g Escherichia coli count in frozen raw Nile tilapia fish samples and a 4.92×10 3 cfu/g Escherichia coli load in asa lebleb (local name) fish origin foods in Arba Minch town, SNNPR, Ethiopia. The Escherichia coli load in raw fish sample was higher than the result of Dhanapal et al, 40 who found 4.9×10 4 cfu/g and lower than the result of Wendwesen et al, 36 who reported 4.63×10 6 cfu/g in frozen raw Nile tilapia fillet samples.…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with the result of Wendwesen et al, 36 who reported 4.63×10 6 cfu/g Escherichia coli count in frozen raw Nile tilapia fish samples and a 4.92×10 3 cfu/g Escherichia coli load in asa lebleb (local name) fish origin foods in Arba Minch town, SNNPR, Ethiopia. The Escherichia coli load in raw fish sample was higher than the result of Dhanapal et al, 40 who found 4.9×10 4 cfu/g and lower than the result of Wendwesen et al, 36 who reported 4.63×10 6 cfu/g in frozen raw Nile tilapia fillet samples. This high load in our study might be due to the result of poor handling during the transportation, and/or poor personal hygiene during harvesting and filleting.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The prevalence of these pathogens in fish varies considerably in different lakes across the country. For instance, Salmonella was reported at prevalence of 5.2% from Hayike 33 , 7.5% from Abaya and Chamo 34 and 30% from Tinike lakes 35 . Similarly, 1.5% 36 and 2.3% 37 prevalence of Shiga toxin producing E. coli O157:H7 were reported from fish samples tested at lake Hayike and Tekeze dam, and lake Hawassa, respectively.…”
Section: Introductionmentioning
confidence: 99%